Does the nonmarket environment influence procurement strategy in agricultural supply chains? - Goulart, Daniel Franco; Perez, Gilberto; Coti-Zelati, Paolo Edoardo (Revista de Negócios, 2024)
We explore in this research the nonmarket environment's influence on procurement strategy. Given the industry's meaningful regulatory framework, the Brazilian biodiesel supply chain was chosen as an empirical analysis object for that discussion. Through the lens of the nonmarket strategy theoretical framework, this paper discusses how the Brazilian biodiesel firms shape their raw-material procurement strategy under the influence of the Social Fuel Stamp regulation. The data collection was based on interviews with the market and nonmarket practitioners and participant observation. Biodiesel firms must shape their procurement strategy to purchase raw household farming materials to fulfill the Social Fuel Stamp requirements. High costs and challenges are noticed from this need. The study concludes that the Brazilian biodiesel supply chain constitutes empirical evidence of the nonmarket strategy theoretical framework relevance. Therefore, senior managers should consider this topic from a strategy conception standpoint. Quantitatively exploring the role of the nonmarket environment over the procurement strategy can be the subject of future research.